Pengaruh Katalis Fe2O3 Pada Tabung Penyimpanan Hidrogen Berbasis MgH2 Melalui Teknik Mechanical Alloying - Andia Fatmaliana; Maulinda Maulinda; Nirmala Sari (Fakultas Teknik, 2020)
Hydrogen is an alternative energy that has a very abundant amount in nature, three-fourths of all elements in nature are hydrogen. Abundance can be developed because it can be converted into electrical energy and is expected to be able to replace fossil materials that are increasingly depleting in the future. For the management of hydrogen, a very safe storage is needed. One of the efforts by inserting hydrogen in certain metals. Magnesium is one material that is able to absorb hydrogen. But it has a disadvantage, namely the absorption and release time is very slow, this is due to the strong bond between hydrogen and magnesium. Several attempts have been intensively studied to improve the properties of Magnesium including the use of materials in the form of nanocrystals with Mechanical alloying techniques and efforts to add certain catalysts are now being actively studied. Research on the addition of Hematite (Fe2O3) catalysts to hydrogen storage materials has been carried out through Mechanical alloying techniques based on MgH2-Fe2O3. Hematite purely derived from nature has been successfully extracted chemically (precipitation method). The milled MgH2-Fe2O3 alloy samples were then analyzed by XRD and showed that the MgH2-Fe2O3 material was successfully reduced to the nanocrystal scale. The addition of catalysts and extended milling time also showed a decrease in desorption temperature.